A chapter a day: Association of book reading with longevity. (September 2016) - Bavishi, Avni; Slade, Martin D.; Levy, Becca R.
Abstract: Although books can expose people to new people and places, whether books also have health benefits beyond other types of reading materials is not known. This study examined whether those who read books have a survival advantage over those who do not read books and over those who read other types of materials, and if so, whether cognition mediates this book reading effect. The cohort consisted of 3635 participants in the nationally representative Health and Retirement Study who provided information about their reading patterns at baseline. Cox proportional hazards models were based on survival information up to 12 years after baseline. A dose-response survival advantage was found for book reading by tertile (HRT2  = 0.83, p  < 0.001, HRT3  = 0.77, p  < 0.001), after adjusting for relevant covariates including age, sex, race, education, comorbidities, self-rated health, wealth, marital status, and depression. Book reading contributed to a survival advantage that was significantly greater than that observed for reading newspapers or magazines (tT2  = 90.6, p  < 0.001; tT3  = 67.9, p  < 0.001). Compared to non-book readers, book readers had a 23-month survival advantage at the point of 80% survival in the unadjusted model. A survival advantage persisted after adjustment for all covariates (HR = .80, p < .01), indicating book readers experienced a 20% reduction in risk of mortality over the 12 years of follow up compared to non-book readers. Cognition mediated the book reading-survival advantage (p = 0.04). These findings suggest that the benefits of reading books include a longer life in which to read them. Highlights: Book reading provides a survival advantage among the elderly (HR = 0.80, p  < 0.0001). Books are more advantageous for survival than newspapers/magazines. The survival advantage of reading books works through a cognitive mediator. Books are protective regardless of gender, wealth, education, or health.